Review of strategies to promote active aging in Ibero-America - Claudia Troncoso Pantoja; Ximena Díaz Martínez; Miquel Martorell Pons; Gabriela Nazar Carter; Yeny Concha Cisternas; Igor Cigarroa Cuevas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
In Latin America, various experiences that promote active aging are recognized, and can be replicated in various communities, as strategies aimed at a better quality of life. The objective of this review is to identify interventions or recommendations aimed at promoting active aging in Ibero-American countries. The search for evidence was carried out in publications of articles available between 2010 and 2019, using the Medline, Scopus, Scielo, Science-Direct, Virtual Health Library, MEDES and Dialnet databases. Recommendations and experiences carried out for this age group include classic activities such as physical activity or health education workshops, but also cultural, tourist, intergenerational, cognitive strengthening actions, intersectoral activities, life stories, place of residence or use of information technologies. Future promotional experiences for this age group should be planned with an integrating perspective of activities that promote healthy living through creation, culture and healthy living.